Pengaruh Meditasi Cinta Kasih Satu Hari Terhadap Kualitas Diri - Fendy Fendy; Mai Triana; Julia Surya (Jurnal Informasi Pengabdian Masyarakat, 2024)
Metta-bhavana is a meditation method intended to cultivate unconditional love for oneself and others. The aim of this research is to find out how participants in a one-day loving-kindness meditation impact their self-quality at Vihara Dhammacakka Jaya, North Jakarta. This research used a quantitative approach by sending questionnaires to 48 subjects aged 16 years and over. The results showed that daily loving-kindness meditation improved various participants' personal qualities. These include feelings of greater calm and peace, higher levels of patience, better relationships with others, and a decrease in negative feelings such as anger and resentment. More than 80% of participants agreed that loving-kindness meditation was beneficial on various self-quality indicators.